Facilitators and Barriers to Movement Integration in Elementary Classrooms: A Systematic Review. Issue 2 (3rd April 2019) - Michael, Robert Dan; Webster, Collin A.; Egan, Cate A.; Nilges, Lynda; Brian, Ali; Johnson, Robert; Carson, Russ L.
ABSTRACT: Purpose : A systematic review was conducted to identify facilitators and barriers to movement integration (MI) in elementary school classrooms.Method : Online databases (Educational Resources Information Center, Google Scholar, PsycINFO, and PubMed) served as data sources for the study. Following the PRISMA guidelines, relevant published research on MI was identified and screened for inclusion in a qualitative synthesis. Content analysis of the included articles ( N = 28) was used to identify themes of MI facilitators and barriers. Facilitators and barriers were then categorized using a social-ecological framework.Results : A total of 12 themes of MI facilitators and barriers were identified and categorized into two social-ecological levels: institutional factors (e.g., administrative support, resources) and intrapersonal factors (e.g., teacher confidence, ease of implementation).Conclusion : This review can inform research and practice aimed at supporting the implementation of MI in elementary classrooms.